Analisis Perkembangan Permukiman di Kecamatan Laweyan Tahun 2006-2015 - Ariyanti, Rieke; , Drs. M. Musiyam, M.TP (2017)
Laweyan Sub-District is the oldest sub-district in rakarta. It is the central of culture heritage in Central Java, one of the most familiar culture heritage is "Kampoeng Batik Laweyan". In the latest decade, the settlement of this subdistrict have been developed because of urbanization. The increasing development of settlement in settled land of Laweyan is started up with research which aims to: Know the distribution and its pattern of settlement developing of Laweyan SubDistrict in last decade from 2006 to 2015 and to know about factor that affect the development. This research method is using descriptive method. The unit of this research is : (1) block, (2) sub-sub district with the population is people in Laweyan Sub-District. The technique for data's accumulation of this research is : (1) primary data accumulation which direct between : (1) get for Landsat DigitalGlobe Image of Laweyan Sub District from 2006 and 2015 using software, (b) observation, (c) i terview with people in Laweyan Sub-District who live in block with land use for settlement which highest, sample from 20-25% using cluster proportional random sampling; (2) secondary data accommodation from institute of government; (3) cumentation. Analysis technique did in maps which have intersect with description and using nearest neighborhood analysis and to know about the developing of pattern of settlement, link that two analysis with factors which effect development settlemet in the Sub-District. The result of this research showed that distribution of settlement is affected by three kinds of land use: (1) Cropping, (2) Vacant Land, and (3) Settlement Expansion. Land use change distributed in whole sub-district and made distribution pattern of settlement. Generally, the development pattern which was formed in whole subsub-district was forming a group, while there some sub-sub-districts were forming dispersion/distribute or uniform. The factors that affect the development are: (1) Population increase, which in the last decade happened, (2) cessibility and Transportation, which pattern was formed group, then street density is become higher, so that the availability of transportation become better, (3) Environment factors or attractions that makes people choose to stay are to look for fine place to stay, near the central of education activity, look for the expansion because of land cost is still cheap, near working place, and want to work themselves. Keywords : Analysis, Development, Settlement.